2008
DOI: 10.1364/ol.33.001575
|View full text |Cite
|
Sign up to set email alerts
|

Security enhancement of double-random phase encryption by amplitude modulation

Abstract: Conventional double-random phase encoding is vulnerable to a chosen or known plaintext attack owing to the linearity of the system. We introduce a technique to break down this linearity with an undercover amplitude modulation in the encryption scheme. As an additional key, this operation can significantly enhance the security of the system. A series of computer simulations have shown the effectiveness of this method and its resistance against the known plaintext attack. The design and parameter choice of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…In this paper, firstly, we use amplitude modulation encryption scheme to break down this linearity [47]. Secondly, main characteristic of the modified encryption scheme: we choose a random phase encoding P 0 as the initial value of iterative process(P 0 is independent).…”
Section: Iterative Algorithm Attacksmentioning
confidence: 99%
“…In this paper, firstly, we use amplitude modulation encryption scheme to break down this linearity [47]. Secondly, main characteristic of the modified encryption scheme: we choose a random phase encoding P 0 as the initial value of iterative process(P 0 is independent).…”
Section: Iterative Algorithm Attacksmentioning
confidence: 99%
“…In particular, efficient hierarchical chaotic image encryption (HCIE) algorithm was analyzed in detail and they concluded that the security of the HCIE against ciphertext-only attack was overestimated. Cheng et al [44] proposed a security enhanced double random phase-amplitude encryption (DRPAE) by adding an undercover amplitudemodulating operation in the Fourier domain. They also demonstrated that the DRPAE can resist the traditional (KPA).…”
Section: Introductionmentioning
confidence: 99%
“…Since the double-random phase encryption (DRPE) algorithm was proposed by Refregier and Javidi in 1995 [1], it has been widely used in the fields of image authentication, hiding, encryption, and watermarking [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. This algorithm can be implemented quickly due to its parallel property.…”
Section: Introductionmentioning
confidence: 99%
“…To make up for the deficiency of DRPE in the Fourier domain, many new methods were proposed [12][13][14][22][23][24][25][26]. In [26], W. Chen and X. Chen used only phase information of an encrypted image resulting from DRPE in the Fourier domain to enhance the security of DRPE.…”
Section: Introductionmentioning
confidence: 99%